'Abroad Was Where It all Happened': Inter-war and Post-war Sponsored Migration to the Commonwealth. Issue 2 (4th March 2022) - Harper, Marjory
ABSTRACT: This comparative study of emigration from Britain to the Old Commonwealth scrutinises the motives and experiences of those who left in the years after the First and Second World Wars respectively, and the objectives and practices of those who encouraged or recruited them. It considers whether official policies and participants' perspectives on settlement in Canada, Australia, New Zealand and South Africa were characterised by continuity between the two periods, or whether there was a significant rethinking of attitudes to Commonwealth migration after 1945. It analyses the direct and indirect legacies of war, and evaluates the impact of the Empire Settlement Act on individuals and institutions during a century when confident imperialism was initially replaced by a more defensive attitude, and ultimately by the end of empire. It finds that the demise of institutional migration schemes reinforced a steady shift from the public perception of emigration as a partially corporate phenomenon to a more personal, individualistic process. The first part of the study makes extensive use of the records of Christ's Hospital, Horsham to demonstrate the particular promotion of dominion emigration to public schoolboys, but also some of the challenges and tensions embedded in that policy. The second part draws on oral testimony from emigrants and recruiters, and evaluates briefly the role of film, radio and television in shaping the volume and direction of emigration.